PROTOCOL: When and how to replicate systematic reviews - Sathya Karunananthan; Lara J. Maxwell; Vivian Welch; Jennifer Petkovic; Jordi Pardo Pardo; Tamara Rader; Marc T. Avey; John Baptiste‐Ngobi; Ricardo Batista; Janet A. Curran; Elizabeth Tanjong Ghogomu; Ian D. Graham; et al. (Campbell Systematic Reviews, 2020)
Abstract This is a protocol for a co‐registered Cochrane and Campbell Review (Methodology). The objectives are as follows: To identify, describe and assess methods for: when to replicate a systematic review; how to replicate a systematic review.